2013
DOI: 10.1155/2013/691840
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent, Delayed Hemorrhage Associated with Edoxaban after Deep Brain Stimulation Lead Placement

Abstract: Factor-Xa inhibitors like edoxaban have been shown to have comparable or superior rates of stroke and systemic embolization prevention to warfarin while exhibiting lower clinically significant bleeding rates. The authors report a case of a man who presented with delayed, recurrent intracranial hemorrhage months after successful deep brain stimulator placement for Parkinson disease while on edoxaban for atrial fibrillation. Further reports on the use of novel anticoagulants after intracranial surgery are acutel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Another study showed that postoperative prophylaxis with or without subcutaneous heparin for venous thromboembolism did not increase the risk for intracranial hemorrhage significantly [ 5 ]. More detailed analysis of the handling of chronic anticoagulation treatment in patients undergoing DBS or with existing DBS systems has been provided mainly in the form of case report or small case series [ 4 , 25 , 31 , 33 , 39 ]. We have reported previously on a patient who received bilateral pallidal DBS for severe chorea due to antiphospholipid antibody syndrome with a need for chronic phenprocoumon treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study showed that postoperative prophylaxis with or without subcutaneous heparin for venous thromboembolism did not increase the risk for intracranial hemorrhage significantly [ 5 ]. More detailed analysis of the handling of chronic anticoagulation treatment in patients undergoing DBS or with existing DBS systems has been provided mainly in the form of case report or small case series [ 4 , 25 , 31 , 33 , 39 ]. We have reported previously on a patient who received bilateral pallidal DBS for severe chorea due to antiphospholipid antibody syndrome with a need for chronic phenprocoumon treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial hemorrhage in patients with DBS and subsequent anticoagulation therapy was reported very rarely. In one patient, high-dose intravenous heparin was administered on the first postoperative day for acute myocardial infarction [ 25 ], and in two other patients, edoxaban was restarted already on day 5 and day 7 after surgery [ 20 , 33 ]. One of these patients also had a recurrent hemorrhage later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors of hemorrhage occurrence can be classified into surgical-and patient-related ones. Surgical-related risk factors include the use of multiple recording microelectrodes or multiple attempts to position the definitive electrode, [6] whereas patient-related risk factors include hypertension, [7] antithrombotic therapy, [8] or advanced age. [9] In this paper, we report a patient with acute hydrocephalus due to intraventricular hemorrhage after DBS procedure.…”
Section: Introductionmentioning
confidence: 99%